An efficient data collection scheme through multi-path routing structures in wireless sensor networks - Luu, Hai Van (2013)
An essential method to overcome the high loss rates of wireless communication in sensor data collection is to use multi-path routing. In this paper, we investigate the construction of multi-path routing structures and develop an enhanced scheme for sensor data collection. In constructing multi-path routing structures, we limit the number of messages that each node transmits and receives in data collection to achieve a required energy efficiency level. Then, we design and analyse an enhanced data collection scheme in which sensor nodes exploit the broadcast nature of wireless transmission to overhear their neighbours. This increases the numbers of data propagation paths from sensor nodes to the base station and improves the robustness of data collection without sacrificing the latency of data collection. Experimental results show that our methods achieve significantly better trade-offs among the robustness, latency and energy efficiency of data collection.